Screening and characterisation of two strains of Pseudomonas aeruginosa from aquaculture and water environment - Samuel, Lihan; Seng, Chiew Toh; Khar, Mun Soh; Natalia, Uyub; Lay, Ching Chai; Müller, Moritz (Malaysian Society for Microbiology, 2018)
Aims: Pseudomonas has been associated with diseases occurring in people with weakened or compromised immune system after exposure to contaminated water. The diseases are commonly treated with antibiotics. However, the bacteria had developed resistances to commonly used antibiotics making treatment a difficult task. Therefore, the continuous surveillance of susceptibility of Pseudomonas especially for the human pathogen P. aeruginosa to commonly clinical and aquaculture farming used antibiotics is important to ensure that serious infections remain susceptible to those antibiotics. Methodology and results: In this study, the bacteria were screened from water, sediment and fish from rivers and aquaculture farms around Kuching, Sarawak. A total number of 38 presumptive P. aeruginosa were isolated using CHROMagarTM Pseudomonas and subjected to a series of biochemical tests. Out of all the isolates tested, only two isolates designated as AS-R10(S) and BK2-OLT2(S) fulfilled the biochemical characteristics of P. aeruginosa. 16S rRNA gene sequencing further confirmed these two isolates as P. aeruginosa based on their 100% similarity with P. aeruginosa strain GD1 and P. aeruginosa strain PA1201 in NCBI database. These two isolates were tested for their susceptibilities against nine common antibiotics used in both clinical and aquaculture farming nowadays: imipenem, piperacillin, meropenem, amikacin, gentamicin, ciprofloxacin, ceftazidime, tobramycin and norfloxacin according to CLSI standard using disk diffusion method. Conclusion, significance and impact of study: The two isolates exhibited total susceptibility to all the antibiotics analysed, suggesting the effectiveness of the antimicrobial agents towards P. aeruginosa isolated from aquaculture and water environment in the study area.